Survive, Learn, Thrive : Strategic Human Capital Investments to Unlock Georgia's Potential - World Bank (World Bank, Washington, DC, 2020)
Human capital is the stock of accumulated knowledge, experience, and attributes that workers bring to and use in the production of goods and services in an economy. Investing in people through quality healthcare, education, social services, and job opportunities develops human capital, which is key to ending extreme poverty and creating more inclusive societies. The state of Georgia’s human capital is of significant concern as it threatens to hold the country back from reaching its growth potential. Recognizing this urgency, the government has begun to set national priorities for accelerating human capital development.This report highlights the state of and trends in human capital development in Georgia today. Its aim is to acknowledge Georgia’s accomplishments, address ongoing challenges, and outline key interventions to help the country in taking the next step in its growth by investing in its most important resource, the Georgian people. Moving from ideation to the implementation of strategic human capital investments will require a whole-of-society approach, an increase in financial commitments, continuous monitoring and learning from results, and the exploitation of technology.